1986
DOI: 10.1099/00221287-132-9-2647
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Toxicity Induced by Lipids and Cell Walls Isolated from Actinomycetes

Abstract: ~~~ ~ ~The possibility was examined that the toxicity induced in mice by Actinomadura madurae, 'Streptomycespelletieri' and Nocardia brasiliensis was due to lipid and cell-wall constituents. Mice were inoculated intraperitoneally with heat-killed bacteria, lipid extracts and cell-wall preparations emulsified in mineral oil : toxicity was evaluated by recording weight loss and deaths. Killed cells and cell-wall preparations of all three actinomycetes produced a pronounced loss of body weight, tissue necrosis, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…or the rapidly growing, soft colony nocardiae (Rhodococcus spp.) (24,86,120,226,227,279,333,335,336,491,614,615,630,729). Tamplin and McClung (661) reported that there appeared to be a relationship between the cellular content of TDM in N. asteroides and virulence.…”
Section: Role Of Mycolic Acids In Nocardia-host Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…or the rapidly growing, soft colony nocardiae (Rhodococcus spp.) (24,86,120,226,227,279,333,335,336,491,614,615,630,729). Tamplin and McClung (661) reported that there appeared to be a relationship between the cellular content of TDM in N. asteroides and virulence.…”
Section: Role Of Mycolic Acids In Nocardia-host Interactionsmentioning
confidence: 99%
“…(24,86,120,226,227,279,333,335,336,491,614,615,630,729). Most of these are composed of large hydroxylated fatty acids (mycolic acids as described above) esterified to the disaccharide trehalose to form a trehalose glycolipid (279).…”
Section: Role Of Mycolic Acids In Nocardia-host Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ekizlerian et al(1986) indicated that heat-killed Actinomadura madurae, 'Streptomyces pelletieri'and Nocardia brasiliensis contain components with toxic and inflammatory properties; producing loss of body weight, formation of inflammatory exudates, granulomas and death when inoculated into mice. The initial chemical analysis of these toxic component showed that they were composed mainly of polysaccharide and the mycolic acid whichwas only detected in the lipid extract of N. brasiliensis.…”
Section: Discussionmentioning
confidence: 99%
“…A group of biologically active and toxic glycolipids have been identified on the surface of bacterial cells of Corynebacterium, Mycobacterium, Nocardia, and Rhodococcus spp. (24,86,120,226,227,279,333,335,336,491,614,615,630,729). Most of these are composed of large hydroxylated fatty acids (mycolic acids as described above) esterified to the disaccharide trehalose to form a trehalose glycolipid (279).…”
Section: Role Of Mycolic Acids In Nocardia-host Interactionsmentioning
confidence: 99%